Vibratory Forces and Their Influence on Mechanical Systems - Majewski, Tadeusz (Journal of Applied Nonlinear Dynamics, 2026)
Several types of vibrating systems experiencing some interesting effects of inertial forces generated by vibrations are studied. The behavior of these systems can be easily predicted when we know how and which vibratory forces are affecting them. One example is a pendulum with a vibrating pivot that changes the position of equilibrium, alters the natural frequency, and the vibratory force stabilizes its inverse position. Sometimes, a rotor might not reach the final velocity due to the resonance because of the breaking vibratory moment, or the rotor speed decreases rapidly if the motor is switched off. If the imbalanced rotor has free elements inside it, then they can freely align their position and compensate the initial rotor imbalance. Also, the free elements of the rotor are able to eliminate its vibration if the rotor is placed on a vibrating base. It is observed that it is easier to move an object if it is on a vibrating surface than when the surface is not moving at all, apparently due to a lower friction force. By controlling the vibration components of the plane, the object's trajectory as well as its velocity can be controlled. This model can be used to simulate the locomotion of living systems or active Brownian particles. ewline A novel method of analysing mechanical systems which allows to explain their dynamic behaviour and allows to predict some effects is described, along with some examples of laboratory tests.